Peningkatan Keterampilan Motorik Kasar melalui Permainan Lompat Tali pada Siswa Kelompok B TK Pertiwi 1 Pengkol, Sragen - Suratmi, Suratmi (Didaktika, 2022)
Gross motor skills are an important aspect for the development and growth of children. Based on the background above, the formulation of the problem in this study was "How to improve gross motor skills through jumping rope in group B TK Pertiwi 1 Pengkol?" The aim of the study was to improve gross motor skills through a game of jumping rope in group B TK Pertiwi 1 Pengkol. The method used is a qualitative method of class action research. The research subjects were taken from group B students of TK Pertiwi 1 Pengkol Tanon District, Sragen Regency with a total of 26 children in three cycles. Based on empirical data obtained through this study, it shows that the average percentage of children in 1 class has increased from before the pre-cycle action was held at 49.81%. After the action was held in cycle I it increased by 73.40%, but these results had not yet reached the indicator of success, namely 80%, for this reason the researchers held a follow-up cycle, namely cycle II, which reached 86.35%. The average percentage obtained by children in 1 class has increased so it is concluded that the gross motor skills of group B children in TK Pertiwi 1 Pengkol Tanon, Sragen Regency can be improved through a game of jumping rope.